Analisis Strategi Pemerintah Daerah dalam Pemberdayaan Masyarakat melalui Peningkatan Industri Kreatif bagi Pelaku Usaha Mikro, Kecil, dan Menengah (UMKM) di Kelurahan Kranji Kecamatan Bekasi Barat - Adinda Rafika; Eka Rofiyanti; Achmad Barlian (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2022)
This study aims to find out about "Local Government Strategy in Community Empowerment through Increasing Creative Industries for Micro, Small and Medium Enterprises (MSMEs) in Kranji Village, West Bekasi District”. This study uses a qualitative approach with descriptive methods to describe and explain in detail the existing phenomena using interview techniques as a supporting instrument. Research on Local Government Strategies in Community Empowerment Through Increasing Creative Industries for Micro, Small and Medium Enterprises (MSMEs) in Kranji Village, West Bekasi District can be measured from Minztberg Strategy Indicators in Afif and Abdullah (2010), namely: Planning, Actions taken, Positioning Angle, Perspective, Resistance, and Effort. The results of the research that has been carried out show that the local government's strategy in empowering the community through increasing creative industries for MSME actors has been carried out according to planning procedures even though the practice in the field has not been optimal due to the lack of overall outreach by stakeholders in the ranks of the Kranji Village. The programs implemented in an effort to empower the community for MSME actors are very useful for increasing the quality of sales and promotion of products sold by providing market outlets in the Kranji sub-district and holding a bazaar program. In addition, the government provides convenience in processing business licenses and provides business capital assistance programs for MSMEs.